Tibial Tuberosity Transposition Fixation with a Locking Plate during Medial Patellar Luxation Surgery: An Ex Vivo Mechanical Study - Eskelinen, Esa V.; Suhonen, Ari P.; Virolainen, Juha V.; Liska, William D. (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objectives The purpose of this study was to compare the load at failure, stiffness and mode of failure between three types of tibial tuberosity transposition fixation techniques: (a) pin and figure-8 tension band wire (Pin-TBW), (b) locking plate with pin and a tension band wire (Plate-Pin-TBW) and (c) locking plate with a pin (Plate-Pin).Methods Six pairs of raccoon dog cadaveric tibiae were tested in Phase I Pin-TBW versus Plate-Pin-TBW and seven pairs in Phase II Plate-Pin-TBW versus Plate-Pin. One limb of each pair was randomly assigned to one of two groups for each phase. A tensile force was applied to the patellar ligament until construct failure.Results Pin-TBW (342N ± 54.7N) failed at a lower load than Plate-Pin-TBW (469N ± 77.3N), p = 0.00748, with all Pin-TBW failing by fracture and the majority of Plate-Pin-TBW failing by rupture of patellar ligament. Pin-TBW group Phase I, normalized with Plate-Pin-TBW Phase I, failed at a lower load than Plate-Pin group Phase II, normalized with Plate-Pin-TBW Phase II, p = 0.00467. There was no significant difference in mean load at failure, stiffness or mode at failure between the groups in the Phase II study.Clinical Significance Although ex vivo mechanical testing does not replicate the postoperative live dog or cat, these results demonstrate lower construct strength of the Pin-TBW construct compared with the Plate-Pin construct in the raccoon dog cadaver model.
Keywords: mechanical testing; patellar luxation; tibial tuberosity transposition; locking plate